Effects of Pre-exercise Acute Vibration Training on Symptoms of Exercise-Induced Muscle Damage: A Systematic Review and Meta-Analysis. Issue 8 (12th August 2022) - Tan, Jingwang; Shi, Xiaojian; Witchalls, Jeremy; Waddington, Gordon; Lun Fu, Allan C.; Wu, Sam; Tirosh, Oren; Wu, Xueping; Han, Jia
Abstract: Tan, J, Shi, X, Witchalls, J, Waddington, G, Lun Fu, AC, Wu, S, Tirosh, O, Wu, X, and Han, J. Effects of pre-exercise acute vibration training on symptoms of exercise-induced muscle damage: a systematic review and meta-analysis. J Strength Cond Res 36(8): 2339–2348, 2022—Exercise-induced muscle damage (EIMD) normally occurs after unaccustomed high-intensity eccentric exercises. Symptoms of EIMD include delayed-onset muscle soreness (DOMS), tenderness, stiffness, swelling, reduced strength, and increased creatine kinase (CK) levels in the blood. Vibration training (VT) may be useful as a pre-exercise intervention in attenuating EIMD on the basis of tonic vibration reflex (TVR) through a more efficient distribution of contractile stress over muscle fibers. The objective of this meta-analysis is to examine the effects of acute VT on symptoms of EIMD when performed as the pre-exercise intervention. Randomized controlled trials (RCTs) published in the 8 databases of Cochrane Library, PubMed, Embase, Web of Science, EBSCO, China National Knowledge Infrastructure, Airiti Library and WanFang Data from 1966 (the earliest available time) to January 2019 were searched. A total of 2, 324 records were identified and 448 articles were screened with the title and abstract. Two investigators identified eligible studies, extracted data, and assessed the risk of bias independently. Review Manager 5.3 designed by Cochrane was used for the current meta-analysis. Six RCTs involving 180 subjects were included in the analysis. A low-to-moderate methodological quality of the included studies was revealed using the physiotherapy evidence database scale. The results showed that acute VT was superior to the control group for the reduction of DOMS on pain visual analogue scale at 24, 48 hours and pressure pain threshold at 24 hours. In addition, superior effects of acute VT were also found on the indirect markers of muscle damage including CK at 24, 72 hours, and lactate dehydrogenase at 24 hours. The current meta-analysis has collated the evidence to demonstrate that receiving acute VT before unaccustomed high-intensity eccentric exercises may be effective in attenuating markers of muscle damage and the development of DOMS when compared with a control group. The possible mechanisms of this effect could be attributed to an improved synchronization of muscle fiber caused by TVR, which could result in even distribution of exterior loads and eventually attenuate disruptions of muscle fibers. In addition, increased blood flow may also be helpful to prevent accumulation of metabolic substances and attenuate subsequent symptoms of EIMD. Vibration training may be used as a pre-exercise intervention to alleviate symptoms of EIMD caused by unaccustomed high-intensity eccentric exercise. Because of the limited quantity and quality of included studies, more high-quality studies are required to ascertain the effect of VT on symptoms of EIMD.